Cellulose and lignin profiling in seven, economically important bamboo species of India by anatomical, biochemical, FTIR spectroscopy and thermogravimetric analysis. (March 2022) - Biswas, Subhadeep; Rahaman, Touhidur; Gupta, Pooja; Mitra, Rumela; Dutta, Smritikana; Kharlyngdoh, Evanylla; Guha, Suman; Ganguly, Jhuma; Pal, Amita; Das, Malay
Abstract: Bamboos, a group of non-timber grasses, offers a great promise for the ligno-cellulosic biomass industry due to their very fast growth resulting rapid accumulation of lignocellulose biomasses, high fibre contents, low maintenance cost and existence of a diverse genetic pool. Despite, not voluminous and significant studies aimed to investigate the anatomy and biochemistry related to the cellulose and lignin synthesis in bamboos. Particularly, there remains a big knowledge gap on the variations of cellulose and lignin contents that exists at the germplasm level. Therefore, this study aimed to analyse chemical composition of ligno-cellulosic biomasses obtained from internode tissues of seven, abundantly available bamboo species of India ( Bambusa balcooa, B. tulda, B. bambos, B. nutans, B. striata, Dendrocalamus giganteus, and D. strictus ) by performing Attenuated Total Reflection-Fourier Transform Infrared (ATR-FTIR) Spectroscopy and Thermogravimetric analysis (TGA). Four anatomical parameters were used to predict 'superior' bamboo species/genotypes with respect to high cellulose vs. low lignin content. Particularly integrated density (ID) of Fast green and Phloroglucinol stains were correlated to the biochemical estimates of cellulose and lignin conducted on 63 samples. Hence the study concludes that stain ID can be used for quick screening of bamboo germplasms having desired ligno-cellulose contents. On the basis of multiple parameters analysed, B. bambos emerged as a reference bamboo for future ligno-cellulose research. Highlights: Seven bamboos analysed using growth patterns, anatomical, biochemical parameters TGA data provides information on thermal stability of bamboo LCB Stain intensity correlated with biochemical estimation of cellulose, lignin Anatomical parameters useful for quick screening large population, elite species B. bambos can be a reference bamboo for future ligno-cellulose research